Порівняння інструментів управління конфігурацією Ansible та Chef - Маслій, В. П. (ХНУРЕ, 2020)
Tools for managing the Chef and Ansible buzz conceived to simplify the setup and servicing of the ten, hundreds and thousands of servers. You can automatically unload these configurations to your server in the middle of the server. This thesis will compare these configuration management tools